Education Marketing Strategy in Al-Amalul Khair Palembang Islamic Junior High School - Febriyanti Febriyanti; Rinovian Rais; Iswahyu Pranawukir; Wira Alvio; Ivan Riyadi (Irfani, 2022)
This study aims to find out about the education marketing strategy carried out by the Al-Amlaul Khair Islamic Junior High School, as well as the factors that influence the education marketing strategy at the Al-Amlaul Khair Islamic Junior High School. This research method is in the form of qualitative descriptive, data collection techniques using observation, interviews, and documentation. The key informant in this study was the principal, and the supporting informants were educators, education staff, students, and the community around the Al-Amlaul Khair Islamic Junior High School. The results of this study indicate that the Al-Amlaul Khair Islamic Junior High School has implemented a fairly good educational marketing strategy, several programs and services are offered and can attract public interest and taste, the promotional activities carried out by the school are quite good and a special team has been formed to promote education. Promotional activities carried out by schools include placing banners, distributing brochures, placing advertisements, and outreach to other schools. There is something unique about the promotion at Al-Amlaul Khair Islamic Junior High School, namely "picking up the ball", in which the school gives a brochure to each student and students distribute it to their respective addresses, if the student succeeds in bringing in a new student, the student will be given a prize. from school.